جماليات التشكيل الإيقاعي ودلالاته في الشعر الشعبي المغاربي قصيدة الشوق للديار المقدسة لعبد العزيز المغراوي أنموذجا - حني, عبد اللطيف; بن وناس, مفيدة (جامعة الوادي - university of Eloued, 2022)
يُعدّ الشاعر عبد العزيز المغراوي من أعلام الشعر الشعبي المغاربي، فقد عالج في شعره الموضوعات الذاتية وأهمها مدح النّبي صلى الله عليه وسلم، بتعابير وقوالب تجلب القارئ وتأسر السّامع وتسترعي اهتمامه، وعليه أسست هذه الدراسة لتغوص في جماليات التشكيل الايقاعي باعتباره أحد التقانات المعنوية والدلالية، محاولين الوقوف على مختلف أبعادها انطلاقا من تشكيل الحروف ثم الألفاظ ثم العبارات، لنقارب ونعايّن هذه البنى الصوتية ومدى تناسقها وانسجامها وقدرتها على نقل الحالة النّفسية للشاعر وتفاعله متخذين قصيدة "الشوق للديار المقدسة" أنموذجا. The poet Abdelaziz Al-Maghrawi is considered one of the prominent Maghreb folk poetry. He dealt in his poetry with subjective topics, the most important of which is the praise of the Prophet, may God’s prayers and peace be upon him, with expressions and templates that attract the reader, captivate the listener, and draw his attention. Accordingly, this study was founded to delve into the aesthetics of rhythmic formation, one of these moral and semantic techniques. Trying to stand on its various dimensions, starting from the formation of letters, then words, then phrases, to approach and examine these phonetic structures and their consistency, harmony and ability to convey the poet’s psychological state and interaction, taking the poem of longing for the holy lands as a model.
مقال
Keywords: التشكيل الايقاعي؛ الموسيقى؛ الدلالات ؛ الشعر الشعبي؛ المغاربي؛ المغراوي.; vocal modulation, Music, semantics, folk poetry, Maghrebi ,Al-Maghrawi.